Region and nation : - Brennan, James P. (Martin's Press, 2000)
In seven essays, Argentine and US historians continue the very recent study of the rest of the country besides Buenos Aires. By shifting the focus to the interior, they complement histories told from the city, show how different the interior is from the metropolitan, challenge city-based history as national history, and demonstrate how events in the provinces have redirected and defined national history. Four maps are provided.